Suicide intervention training with law enforcement officers. Issue 4 (17th May 2021) - Osteen, Philip J.; Ohme, Karen; Morris, R.C.; Arciniegas, Jorge; Frey, Jodi J.; Woods, MaKenna; Forsman, R. Lane
Abstract: Law Enforcement Officers' (LEO) interactions with people facing mental health crises have risen exponentially since the era of deinstitutionalization. On average, about 10% of the individuals law enforcement interacts with daily have mental health challenges. Several factors influence the outcome of these interactions, not least of which is an officer's role as a gatekeeper as well as their training related to people with mental health challenges. We hypothesized that participating in the online QPR Training for Law Enforcement Officers would be associated with improved knowledge about suicide, attitudes to suicide and suicide intervention, and self‐efficacy. Additionally, we hypothesized that these outcomes would be associated with greater use of intervention skills when encountering individuals at risk for suicide in the community. Results of our longitudinal analysis find that most of the participating officers reported some prior training and yet demonstrated statistically significant improvements in knowledge and attitudes after controlling for previous training. No significant changes were observed in LEO's use of intervention skills following training. We conclude by suggesting that there is substantial need for increased training; and offering possible conceptual and empirical explanations for the observed results.